(untitled) (Damascus University Journal of agriculture sciences, 2024)
This research was conducted at the laboratories of Food Sciences Department, Faculty of Agriculture, Damascus University, and the Central Grain Laboratory, Ministry of Internal Trade and Consumer Protection, with the aim of studying the effect of adding different types of fat substitutes (rice starch and pectin) on the rheological properties of wheat flour dough prepared for the preparation of dry biscuits, and evaluating the quality characteristics (processing and sensory properties) of biscuits prepared using fat substitutes. The results of the rheological analysis of doughs prepared for the manufacture of dry biscuits showed the negative effect of replacing the fatty substance, whether with rice starch or pectin, as it was observed that the tenacity increased and consistency decreased with the high rate of replacement, and the used fat substitutes did not have the ability to maintain the properties of the dough (tenacity and consistency) during the test time compared to the basic used fatty substance, but pectin when used as a substitute for fat exhibited better rheological properties than rice starch. Moreover, the results of the research indicated that the replacement of fat with the used substitutes at high rates led to a decrease in the rheological properties, while the replacement ratio of 25% was appropriate and close to the readings of the control. On the other hand, the results of the statistical analysis showed a highly significant effect of the process of replacing vegetable fat with the studied fat substitutes on the processing properties of biscuit, where the average diameter and the average thickness of the biscuit piece increased, while the spread ratio and hardness decreased when the replacement ratio increased. Furthermore, the results of the sensory analysis showed that the surface of the biscuits in the samples in which the fat was replaced became coarse and darker in color with the increase in the percentage of replacement. The overall quality score indicated that the fat used to make biscuits could be replaced with fat substitutes, such as rice starch and pectin, by up to 25% without affecting the sensory properties of biscuits.